Between self-governance and political participation - Wutti, Daniel (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The article presents the political participation of the Slovene minority in Carinthia from the plebiscite of 1920 until the present. The changed electoral franchise agreed by the ruling parties in Carinthia in the 1970s blocked attempts of the minority to be incorporated adequately in a broader political sphere. The political actors of the minority followed two strategies: one of building up their own political structures in local parties and one of joining Austrian and Carinthian mainstream parties. This paper gives a brief overview of the minority's struggle for self-governance and political participation. It introduces the organisational structure of the minority and its opportunities for political participation. Its aim is to deal with the question of which factors led to political differentiation and how to assess this.
Keywords: Austria; Avstrija; narodne manjšine; koroški Slovenci; Carinthian Slovenes; politična participacija; zastopstvo manjšine; diferenciacija